1375. Characterization of Recurrent Central Line-associated Bloodstream Infections at Texas Children's Hospital. (31st December 2020) - Foster, Catherine; Marquez, Lucila; Koy, Tjin; Campbell, Judith
Abstract: Background: Recurrent central line-associated bloodstream infections (CLABSI) in children present a unique challenge to infection prevention efforts but guidelines for management are lacking. Methods: We reviewed CLABSI data at Texas Children's Hospital (TCH) from fiscal years (FY) 2017-2019. A chart review to characterize clinical features, risk factors, and outcomes of patients with recurrent CLABSIs in FY2019 was performed. Descriptive statistics and Fisher's exact test were used. Results: Recurrent CLABSIs increased from FY 2017-2019 [20% (26/126) to 33% (44/131)] ( P =0.03). In FY2019, 15 patients accounted for 44 CLABSIs (Figure 1). Underlying conditions included aplastic anemia (4), hemophagocytic lymphohistiocytosis (3), malignancy (4), genetic disease (2), congenital heart disease (1) and biliary atresia (1). Two-thirds of the CLABSIs occurred in the setting of severe neutropenia (ANC < 100 cells/mm 3 ) though only 16 (36%) were classified as mucosal barrier injury. The median time between line insertion and date of infection was 41 days (range 1-105). Line type included central venous catheters (25, 57%), peripherally inserted central catheters (17, 39%) and implantable ports (2, 5%). Most lines (80%) had double lumens. The most common organisms included: Gram-negative bacilli (15), coagulase negative staphylococci (14), viridans group streptococci (6) Candida spp. (5), Enterococcus faecalis (3) and Staphylococcus aureus (3). Four CLABSIs were polymicrobial. Patients with >2 CLABSIs were more likely to have subsequent infections with the same organism as compared to patients with only 2 CLABSIs ( P =0.01). Lines were removed promptly (19, 43%), had delayed removal (removal >72 hours from infection date) (10, 23%) or remained in place (15, 34%). Lines were removed for all episodes of fungemia (5/44) and for most Gram-negative infections (10/12). Six of 7 Escherichia coli CLABSIs were breakthrough fluoroquinolone-resistant infections in patients on levofloxacin. Single Episode and Recurrent CLABSIs at Texas Children's Hospital for Fiscal Year 2019 Conclusion: Recurrent CLABSI accounted for a third of CLABSIs in FY2019. Line mismanagement was not a key contributor to recurrent CLABSI. Breakthrough CLABSIs in patients on levofloxacin prophylaxis need further investigation. For patients with CLABSIs due to Staphylococci decolonization may be considered. Disclosures: All Authors : No reported disclosures